(untitled) (American Journal of Human Psychology, 2025)
This study explored how the trainers’ characteristics and the trainees’ motivational orientation influenced the transfer of training among employees in the Financial Technology industry. This work is attached to Sustainable Development Goal (SDG) 8, concentrating on decent work and economic growth. Despite heavy investments in corporate trainings, many organizations struggle to convert training into on-the-job behavior; drawing on Self-Determination Theory, this study tested how trainer characteristics (interaction, attitude, competency) and trainees’ motivational orientation (intrinsic, extrinsic) jointly predict transfer of training among Philippine fintech sales agents using a correlational–predictive design with simple random sampling, validated instruments, and SPSS analyses (Pearson r; multiple regression). Descriptively, trainer characteristics (M = 3.61), motivational orientation (M = 3.66), and transfer (M = 3.67) were moderate. Trainer characteristics strongly correlated with transfer (r = .839, p < .001), as did motivational orientation (r = .906, p < .001); the regression model explained 81.3% of variance in transfer (R² = .813, p < .001), with motivational orientation exerting the larger standardized effect (β = .675, p < .001) compared with trainer characteristics (β = .278, p < .001). Findings extend transfer theory by quantifying the relative contribution of motivation vis-à-vis trainer qualities in a fintech context and offer actionable levers for industrial counseling practice: autonomy-supportive design, relevance framing, structured coaching and feedback, and recognition systems that strengthen internalization, thereby maximizing behavior change at work.